A prospective cohort study on cognitive and psychological outcomes in COVID-19 ICU survivors at 3 months of follow up - Thomas, Merlin; Hameed, Mansoor; Hussein, Mousa; George, Saibu; Rajalekshmi, M. R.; Akram, Jaweria; Sharma, Rohit; Al Adab, Aisha Hussain O.; Ahmad, Mushtaq; Singh, Rajvir; Raza, Tasleem (Frontiers in Medicine, 2024)
Objective The Outcomes – Short and Long term in ICU patient with COVID-19 “OUTSTRIP COVID-19” study was initiated to assess overall mortality, physical and psychiatric co-morbidities, reduction in lung function, and the ability to return to work post-ICU discharge with a follow-up period of 2 years in COVID-19 patients admitted to ICUs in Qatar. This paper focuses on the prevalence of cognitive impairment, depression, anxiety, and stress at baseline and 3 months after ICU discharge. Methods This prospective cohort study included 100 ICU survivors reviewed at baseline within 7 weeks of ICU discharge, with a 3-month follow-up. Demographics, clinical characteristics, and relevant medical history were collected at baseline. Cognitive outcomes were assessed using the Montreal Cognitive Assessment-Basic (MoCA-B) tool, while psychological outcomes were evaluated using the Depression Anxiety and Stress Scale-21 (DASS-21). Results At baseline, 72% of ICU survivors exhibited mild cognitive impairment, which significantly improved to 56% at 3 months. However, severe cognitive impairment persisted in 20% of survivors at 3 months. For psychological outcomes, the mean depression score remained below 9 (5.64 ± 6.90) at both time points, with no significant change. At baseline, 25% of survivors had clinical depression, which reduced to 16% at 3 months. The mean anxiety score at baseline (9.35 ± 8.50) significantly decreased to 6.51 ± 7.74 (p = 0.002) at 3 months. Anxiety was not reported by 48% of survivors at baseline and this increased to 66% at 3 months. Severe to extremely severe anxiety decreased from 19% to 12% during the same period. The mean stress score at baseline (8.34 ± 8.07) did not significantly change at 3 months. At baseline, 18% experienced stress, which decreased to 12% at 3 months, with 5.3% facing severe to extremely severe stress. Conclusion COVID-19 ICU survivors experience significant cognitive impairment, anxiety, and stress. While cognitive impairment and anxiety showed improvements at 3 months, depression and stress remained unchanged. These outcomes strongly emphasize the requirement for thorough post-ICU care and comprehensive mental health assistance for individuals recovering from COVID-19. Customized interventions and additional research endeavors are crucial to effectively manage the cognitive and psychological consequences faced by these patients. The exploration of telemonitoring and innovative approaches can offer avenues to enhance the overall quality of life for survivors. Further investigation should encompass extended timeframes to analyze prolonged effects and consider the broader socioeconomic impact.